2014
DOI: 10.1016/j.brainres.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and phenotype of TrkB oligodendrocyte lineage cells in the adult rat spinal cord

Abstract: The distribution and phenotype of a previously undescribed population of nonneuronal cells in the intact spinal cord that expresses TrkB, the cognate receptor for brain derived neurotrophic factor (BDNF) and neurotrophin 4 (NT-4), were characterized by examining the extent of co-localization of TrkB with NG2, which identifies oligodendrocyte progenitors (OPCs) or CC1, a marker for mature oligodendrocytes (OLs). All TrkB nonneuronal cells expressed Olig2, confirming their role in the OL lineage. Similar to OPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…In the rat spinal cord, over 80% TrkB-expressing cells co-express CC1, indicating differentiated OLs. A small OPC pool also show TrkB immunoreactivity, suggesting a function in growth (Coulibaly et al, 2014). Ablation of the TrkB receptor in the oligodendroglial lineage disrupts myelination, and indirectly increases the density of OPCs (Wong et al, 2013).…”
Section: Strategies For Improving Protection and Repairmentioning
confidence: 99%
“…In the rat spinal cord, over 80% TrkB-expressing cells co-express CC1, indicating differentiated OLs. A small OPC pool also show TrkB immunoreactivity, suggesting a function in growth (Coulibaly et al, 2014). Ablation of the TrkB receptor in the oligodendroglial lineage disrupts myelination, and indirectly increases the density of OPCs (Wong et al, 2013).…”
Section: Strategies For Improving Protection and Repairmentioning
confidence: 99%
“…These TrkB expressing cells, which are increased in number by the peripheral axon injury, may represent a population of OL lineage cells that has upregulated TrkB expression while ‘in transition’ from a progenitor to a mature OL state. We are confident that the TrkB cells are of the OL cell lineage since all non-neuronal cells expressing full length TrkB were shown to also express Olig2 (18), and astrocytes express only the truncated isoform of TrkB (23, 24). …”
Section: Discussionmentioning
confidence: 93%
“…In an effort to determine which cell type in the OL lineage was responsible for the increased number of plaques per cell, double labeling of Cx32 with the OL markers TrkB [17,18], CC1 [19], or NG2 [20] was carried out. In a recent study from our lab, the majority of TrkB cells (>80%) were shown to colocalize CC1, indicating their mature phenotype [18], yet a proportion of TrkB cells may represent a separate pool of OL linage cells [18] and thus TrkB cells were considered separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations